A survey of poison center knowledge and utilization among urban and rural residents of Arizona. (2015) - Otaluka, Onyinye N.; Corrado, Rachel; Brooks, Daniel E.; Nelson, Deborah B.
Abstract: Background: Poison control centers (PCCs) hold great potential for saving health care resources particularly by preventing unnecessary medical evaluations. We developed a survey to better identify the needs and experiences of our service community. We hope to use these data to improve PCC outreach education and overall use of our services. Method: A written questionnaire was developed in English and then translated into Spanish. Subjects agreeing to participate were then asked two verbal questions in English: are you at least 18 years of age? And; in what language would you like to complete the questionnaire; English or Spanish? All questionnaires completed by subjects ≥18 years of age were included. Questionnaires with missing responses, other than zip code, were included. Data collected include gender, age, zip code, primary language, ethnicity, education, health insurance status and experiences with the PCC. Subjects were not compensated for participation. Arizona zip codes were divided into "rural" or "urban" based on a census data website. Percentages and odds ratios were determined based on completed responses. Smaller subgroups, for some variables, were combined to increase sample sizes and improve statistical relevance. Results: Overall, women and subjects with children at home (regardless of ethnicity) were significantly more likely to have heard of the PCC although Blacks and Spanish-speakers were significantly less likely to have heard of the PCC. Similarly, respondents with children at home and those reporting a prior home poisoning (regardless of ethnicity) were significantly more likely to have called the PCC. Blacks were significantly less likely to have called the PCC. These findings were similar among people living in urban zip codes but not statistically significant among rural responders. Conclusions: Based on a small survey, race and language spoken at home were variables identified as being associated with decreased awareness of poison centers. Focusing on these specific groups may assist in efforts to increase PCC penetrance, particularly among urban communities.